2020
DOI: 10.1155/2020/3012198
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEvaluation of Curcumin-Encapsulated Chitosan Nanoparticles against Feline Infectious Peritonitis Virus and Pharmacokinetics Study in Cats

Abstract: Feline infectious peritonitis (FIP) is an important feline viral disease, causing an overridden inflammatory response that results in a high mortality rate, primarily in young cats. Curcumin is notable for its biological activities against various viral diseases; however, its poor bioavailability has hindered its potential in therapeutic application. In this study, curcumin was encapsulated in chitosan nanoparticles to improve its bioavailability. Curcumin-encapsulated chitosan (Cur-CS) nanoparticles were synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Of the 46 research papers retrieved for qualitative synthesis, several investigated nanomaterials potential against animal models and cell lines of 3 genera of Coronaviridae family causative illness in animals (n = 6) and humans (n = 6), including alpha-coronavirus (n = 6), beta-coronavirus (n = 5), and gammacoronavirus (n = 1). Related to 6 types of coronavirus originated in animals, were found 12 articles reporting nanomaterials against transmissible gastroenteritis virus (TGEV), [58] avian infectious bronchitis virus (IBV), [59] feline coronavirus (FCoV), [60] murine hepatitis virus (MHV), [61] type II feline infectious peritonitis virus (FIPV), [62,63] and porcine epidemic diarrhea virus (PEDV). [64][65][66][67][68][69] Concerning the 6 types of coronavirus cause illnesses in people were found 33 different studies reporting the role of nanomaterials against human coronavirus NL63 (HCoV NL63), human coronavirus OC43 (HCoV OC43), [61,70] human coronavirus 229E modified containing a renilla luciferase reporter gene (HCoV-229E-Luc), [71] human MERS-CoV, [72,73] human SARS-CoV, [74] and novel human SARS-CoV-2.…”
Section: Main Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 46 research papers retrieved for qualitative synthesis, several investigated nanomaterials potential against animal models and cell lines of 3 genera of Coronaviridae family causative illness in animals (n = 6) and humans (n = 6), including alpha-coronavirus (n = 6), beta-coronavirus (n = 5), and gammacoronavirus (n = 1). Related to 6 types of coronavirus originated in animals, were found 12 articles reporting nanomaterials against transmissible gastroenteritis virus (TGEV), [58] avian infectious bronchitis virus (IBV), [59] feline coronavirus (FCoV), [60] murine hepatitis virus (MHV), [61] type II feline infectious peritonitis virus (FIPV), [62,63] and porcine epidemic diarrhea virus (PEDV). [64][65][66][67][68][69] Concerning the 6 types of coronavirus cause illnesses in people were found 33 different studies reporting the role of nanomaterials against human coronavirus NL63 (HCoV NL63), human coronavirus OC43 (HCoV OC43), [61,70] human coronavirus 229E modified containing a renilla luciferase reporter gene (HCoV-229E-Luc), [71] human MERS-CoV, [72,73] human SARS-CoV, [74] and novel human SARS-CoV-2.…”
Section: Main Findingsmentioning
confidence: 99%
“…[45] We collected data from several nanostructures' types studied against the coronavirus cited above as nanotubes, nanorods, nanoparticles, nanostars, nanowires, nanocrystals, nanosheets, nanogels, nanospheres, nanocapsules, nanoclusters, and nanostructured lipid carriers (NLCs). Of these, were identified the following nanotechnology-based approaches: bioconjugated carboxyl quantum dots (QDs); [74] silver nanomaterials; [58,60,69,80,96,97] synthetic virus-like particles (sVLPs); [77] gold nanoparticles; [59,77] biopolymeric/biodegradable polymeric nanoparticles and hydrogels (e.g., chitosan, collagen, poly(ethylene glycol) (PEG), poly lactic-co-glycolic acid (PLGA), and poly(hydroxyethyl) methacrylate); [61,62,63,79,[85][86][87]91,93] carbon quantum dots (CQDs) [71] and cationic carbon dots based on curcumin (CCM-CDs); [68] glutathione(GSH)-capped silver-sulfide nanoclusters (GSHcapped Ag 2 S NCs); [64] gold nanorod-based heptad repeat 1 (HR1) peptide; [72] antigen and adjuvant-loaded hollow polymeric nanoparticles; [73] bovine serum albumin (BSA)-coated tellurium nanoparticles (Te/BSA NPs) with a unique triangular star shape (Te/BSA nanostars); [65] GSH-modified zinc-sulfide nanoparticles (ZnS NPs); [66] glycyrrhizic-acid-based carbon dots (Gly-CDs); [67] multi-walled carbon nanotubes (MWCNTs) with target functions; [83] metal-decorated single-wall carbon nanotubes (SWCNTs); [100] NLCs; [88] graphene oxide; [60,82,92] iron oxide nanoparticles (IONPs), [75] functionalized graphene sheets;…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the therapeutic efficiencies of different antiviral agents and immunomodulatory medicines against FIPV have been studied in previous studies, but most were to avail. Nevertheless, recent studies have shown that itraconazole, a common antifungal drug, GC376 3C-like protease inhibitor, and nucleoside analogue GS-441524, are effective in inhibiting infection in cats with naturally occurring FIP [ 129 ].…”
Section: Application Of Nanomaterials In the Treatment Of Feline Infectious Peritonitis Virusmentioning
confidence: 99%